The Characters of The Hippopotamidae from Java (Indonesia) Based on Skull and Tooth Analyses - Unggul Prasetyo Wibowo; Yahdi Zaim; Aswan Aswan; Mika Rizki Puspaningrum (Geological Agency, 2026)
Hippopotamidae are known to have lived in the island of Java based on the presence of their fossils. Several researchers have described and concluded that there are three species of Hippopotamidae in the island of Java, but there are also those who argue that the three types of Hippopotamidae are of the same species. These differences give rise to further discussion regarding what species lived in the island of Java in the past. Twenty Hippopotamidae fossil specimens including twelve specimens recently discovered, and previously undescribed specimens collected form stratigraphic context from Java were analyzed in this study and compared with previous literature. This study of Hippopotamidae fossils is based on skulls and teeth where the number of incisor teeth is one of the distinguishing characters which shows that all Hippopotamidae fossils in Java Island are from the genus Hexaprotodon. Our evidence shows that there are two types of Hexaprotodon in Java, namely the relatively small Hexaprotodon in The Gelasian-Calabrian-Chibanian Pleistocene, and a larger Hexaprotodon of Late Chibanian-Late Pleistocene age. Based on its anatomy, the small Hexaprotodon from Java is called Hexaprotodon sivajavanicus, while the large Hexaprotodon from Java is called Hexaprotodon megakendengensis